Uma partida de xadrez com Saussure e Lacan: uma análise da relação entre sujeito e linguagem - Rocha, Ina Mirely Oliveira da (2010)
This work aims to discuss the relationship between the subject and the language in the rapprochement between linguistics and psychoanalysis. Based on the studies of Saussure's linguistic sign and Lacan s signifier, we seek to observe the subject as a result of the movement of signifiers. This is not an analysis of the subject of the unconscious, but an attempt to understand the subject as an effect of language as a result of movements of sign and signifier. We present, in part, the analysis of Lacan's short story "The Purloined Letter," regarding the subject as a result of movement of signifiers, and provide an important contribution based on Saussurean linguistics, whose studies concern the language as a system, taking Saussure s metaphor of the chess game as our basis. We observe the movements of the characters of the story and their relationship with the movements of the letter, the letter which entitles the tale. We demonstrate the Saussurean approach for language as a system and its operation, highlighting all the concepts inherent to the system, going from the general to its constituent units. On the side of psychoanalysis, we assume the signifier in Lacan, relating the movements of this signifier to the movements of the Saussurean sign. It is from this relationship that we try to understand the subject as an effect of language, the subject that we address in this interface. As a result of this rapprochement between Saussurean linguistics and Lacanian psychoanalysis, we bring the subject, no longer the one of the unconscious or the one of language, but a subject resulting from the movements in the short story "The Purloined Letter", based on the theoretical dialogue developed in this dissertation.